2018
DOI: 10.1038/s41598-018-30005-8
|View full text |Cite
|
Sign up to set email alerts
|

Soil Properties Drive Microbial Community Structure in a Large Scale Transect in South Eastern Australia

Abstract: Soil microbial communities directly affect soil functionality through their roles in the cycling of soil nutrients and carbon storage. Microbial communities vary substantially in space and time, between soil types and under different land management. The mechanisms that control the spatial distributions of soil microbes are largely unknown as we have not been able to adequately upscale a detailed analysis of the microbiome in a few grams of soil to that of a catchment, region or continent. Here we reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
81
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(110 citation statements)
references
References 57 publications
18
81
1
Order By: Relevance
“…Here, we focus on responses of soil microbial communities, which can be strongly affected by land-use legacies and restoration practices (e.g. Barber, Chantos-Davidson, Amel Peralta, Sherwood, & Swingley, 2017;Freschet, Östlund, Kichenin, & Wardle, 2014;Hui et al, 2018;Jangind et al, 2011;Ma, De Frenne, Boon, et al, 2019;Xue, Carrillo, Pino, Minasny, & McBratney, 2018) but are poorly studied taxa in these fields (e.g. Brudvig, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we focus on responses of soil microbial communities, which can be strongly affected by land-use legacies and restoration practices (e.g. Barber, Chantos-Davidson, Amel Peralta, Sherwood, & Swingley, 2017;Freschet, Östlund, Kichenin, & Wardle, 2014;Hui et al, 2018;Jangind et al, 2011;Ma, De Frenne, Boon, et al, 2019;Xue, Carrillo, Pino, Minasny, & McBratney, 2018) but are poorly studied taxa in these fields (e.g. Brudvig, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, underlying site properties might be mistakenly interpreted as agricultural legacy effects, when in fact they are simply consequences of the land-use decision-making process. Controlling for these land-use biases is particularly important for resolving how soil microbial communities respond to land-use legacies, given soil microbes' responsiveness to soil conditions (Fierer & Jackson, 2006;Lauber, Strickland, Bradford, & Fierer, 2008;Ma, De Frenne, Vanhellemont, et al, 2019;Ma et al, 2018;Xue et al, 2018). Here, we control for land-use biases through a study design where post-agricultural plots and remnant plots with no known history of agriculture are paired in space, resulting in no bias in underlying soil types (Brudvig, Grman, Habeck, Orrock, & Ledvina, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising since soil nutrients have no direct influence on soil volatiles. Yet, they might indirectly influence the physiology of volatile emitters and shape soil's microbiome (Faoro et al, 2010;Wang et al, 2017;Xue et al, 2018), potentially explaining the small effect observed here in the soil volatilome. Indeed the relative proportion of available carbon to nitrogen (C:N) or to phosphorus (C:P), and the ratio of nitrogen to phosphorus (N:P) are known to impact plant biomass and metabolism (Elser et al, 2010;Güsewell, 2005;Huarancca Reyes et al, 2018;Zheng, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…Climate gradients appear to significantly affect the diversity and function of soil microbial communities, likely due to differences in air temperature, soil moisture, and plant community composition with increasing latitude (Garcia-Pichel et al, 2013;Staddon et al, 1998;Wu et al, 2009) and elevation (Bryant et al, 2008;Yang et al, 2014). Also, many studies have found significant differences in microbial community composition and/or diversity across environmental gradients at large spatial scales (Fierer and Jackson, 2006;Garcia-Pichel et al, 2013;Griffiths et al, 2011;Lauber et al, 2009;Xue et al, 2018).…”
Section: Introductionmentioning
confidence: 99%